YIELD AND QUALITY INDICATORS OF WINTER WHEAT GRAINS DEPENDING ON DOSES OF FERTILIZERS APPLIED - Кудрявицкая, Алина (SWorldJournal, 2022)
Studies on meadow-chernozem carbonate soil have shown that long-term use of mineral fertilizers against the background of organic aftereffects provides an increase in grain yield of regionalized spring wheat variety Myronivska Yara by 1.73 t / ha. Yield a